The objectives of macro-economic policy - Dasgupta, Ajit Kumar; Hagger, A. J. (London : Macmillan, 1971)
This book is a fairly advanced text in macro-economics written for graduate and final year undergraduate students. It has a strong British emphasis: British institutions provide the framework, the problems selected for discussion are British problems, and British empirical research is drawn on wherever possible.
Label mounted on t.p.: Fernhill House, Ltd., New York, importers & distributors of books.
Includes bibliographical references and index.
hza 27/06/2018
Loans
Keywords: Economic policy; Macroeconomics; Great Britain